Ritratto di una mostra: 'Architettura-città', Mostra Internazionale di Architettura, XV Triennale di Milano - Iannello, Matteo (Opus Incertum, 2024)
Opened in September 1973 as part of the exhibitions organized for the 15th Milan Triennale, the section Architettura-città was curated by Aldo Rossi, Franco Raggi, Massimo Scolari, Rosaldo Bonicalzi, Gianni Braghieri, and Daniele Vitale. The accompanying photo album presents a selection of thirty photographs taken in 1973 by Valerio Castelli during the exhibition’s preparation, a true shipyard portrait capable of restoring in the strong contrast of black and white both the “decidedly cold and rigorous” set-up and the passionate unfolding of daily work, in which Aldo Rossi, Gianni Braghieri, Franco Raggi, Massimo Scolari, Agenore Fabbri, Fabio Reinhart, and Arduino Cantafora, among others, appear.